PENGARUH PERENDAMAN DALAM LINGKUNGAN AIR LAUT TERHADAP SIFAT MEKANIK KOMPOSIT BERPENGUAT SERAT KEVLAR SEBAGAI BAHAN BAKU MATERIAL FLOAT PESAWAT AMPHIBI - Supardi, Nurul Iman; Adiansyah, Zeta; Hestiawan, Hendri (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2020)
Kevlar fibers have several advantages compared to other synthetic fibers, such as high tensile strength and relatively low density because it is composed of hydrogen bonds. This study aims to compare the mechanical strength of Kevlar fiber reinforced composites before and after immersion in a seawater environment as raw material for amphibious aircraft float materials. The materials used in this research consist of kevlar fiber, vinylester resin and methyl ethyl ketone peroxide catalyst. Composites manufactured by the vacuum infusion technique. The fibers were arranged in a mold, then a vacuum process was carried out to attract the resin stream. Tensile and shear tests were carried out before and after immersing the composites in a sea water environment at room temperature for 264 hours. Tensile test specimens refer to the ASTM standard of D3039, while the shear test specimens refer to the ASTM standard of D5379. The tensile strength of the kevlar fiber reinforced composites before immersion is 421.2 MPa. After immersion in a seawater environment, the tensile strength of the composite decreased to 389.3 MPa or decreased by 7.5%. Meanwhile, the shear strength of Kevlar fiber reinforced composites after immersing in a sea water environment did not change significantly from 14.6 MPa to 14.46 MPa or a decrease of 1.6%.